2019
DOI: 10.22458/urj.v11i3.2724
|View full text |Cite
|
Sign up to set email alerts
|

El Armadillo, Cabassous centralis (Cingulata: Chlamyphoridae) en agroecosistemas con café de Costa Rica

Abstract: Introducción: El armadillo Cabassous centralis se clasifica como una especie con Datos Insuficientes que se encuentra desde México hasta el norte de América del Sur. Objetivo: Ampliar la distribución ecológica de C. centralis. Métodos: Colocamos cuatro cámaras trampa en sitios estratégicos como fuentes de alimentación, madrigueras, cuerpos de agua y transición al bosque secundario, en San Ramón, Costa Rica. Resultados: Obtuvimos un registro de C. centralis en la transición entre la plantación de café y el bosq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…We interpret the record in light of this sequence of events as indicative that, with the return of original vegetation, there also has been some restoration of fauna, including rare species, such as the northern naked-tailed armadillo. Third, there have been few previous sightings of C. centralis in the country, including a recent one in a disturbed area in San Ramón (Sánchez and Monge 2019). Here, we report it from four additional sites; however, northern naked-tailed armadillos are not commonly seen or captured, which may be due to its secretive habits and it appears to be particularly elusive (Superina and Abba 2018).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We interpret the record in light of this sequence of events as indicative that, with the return of original vegetation, there also has been some restoration of fauna, including rare species, such as the northern naked-tailed armadillo. Third, there have been few previous sightings of C. centralis in the country, including a recent one in a disturbed area in San Ramón (Sánchez and Monge 2019). Here, we report it from four additional sites; however, northern naked-tailed armadillos are not commonly seen or captured, which may be due to its secretive habits and it appears to be particularly elusive (Superina and Abba 2018).…”
Section: Discussionmentioning
confidence: 67%
“…In Costa Rica, this species generally has been difficult to observe and considered rare (Mora 2000). A photograph of this armadillo was recently obtained in a camera trap at an altered site in San Ramón de Alajuela (Sánchez-Brenes and Monge 2019). These authors pointed out that the northern naked-tailed armadillo currently is observed in altered habitats because it is threatened by several anthropogenic factors, including land use changes and hunting.…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, P. concolor puede ser un indicador de buena salud del ecosistema (Crawshaw & Quigley, 2002;Cortes-Marcial & Briones-Salas, 2014). Además, las especies C. centralis y G. vittata (especies con escasos registros), encontrados en este estudio, fueron los primeros avistamientos para Costa Rica en agroecosistemas con café (Sánchez-Brenes & Monge, 2019;Sánchez-Brenes & Monge, 2022), lo cual refuerza la biodiversidad de este cafetal.…”
Section: Discussionunclassified
“…Cabassous centralis (Miller, 1899) es una de las seis especies de armadillos presentes en Colombia, con una distribución estrictamente transandina, y cuyo rango global abarca Centroamérica y parte del norte de Suramérica entre 0 y 3018 m.s.n.m. (Cruz-Rodríguez et al 2011;Solari et al 2013;Tirira et al 2014;Ramírez-Chaves et al 2016;Soriero et al 2018;Aya-Cuero et al 2019;Sánchez-Brenes & Monge 2019;Sánchez-Soto et al 2020). En Colombia se distribuye en las provincias biogeográficas de: Chocó-Magdalena, Cinturón Árido Caribeño, Macizo de la Sierra Nevada de Santa Marta y en gran parte de la Provincia Norandina (Hernández et al 1992;Alberico et al 2000;Cruz-Rodríguez et al 2011;Tirira et al 2014;Aya-Cuero et al 2019;Chacón-Pacheco et al 2019;Santos et al 2019; Figura 1).…”
unclassified